A Brief Comparative Study on Tragedy in Desire Under the Elms and in the Javanese Chronicle Account of Rara Oyi - Widiarti, Tri Rini; Susena, Bambang; Fajria, Astry (Ahmad Dahlan Journal of English Studies, 2017)
ABSTRACTThis paper is aimed at analyzing tragedy in a play entitled Desire Under the Elms portraying the primitive desires that influence several characters of the afore-mentioned play in the 1920s New England, and also that in a Javanese chronicle account of Rara Oyi that happened during the reign of Sunan Amangkurat I from 1646 to 1677 in the kingdom of Islamic Mataram.   Tragedy discussed in this paper is an occurrence that involves people of high status or people of high nobility, as well as ordinary people, who suffer and whose lives lead to their downfall partly because of the trouble they are unable to get rid of. The play Desire Under the Elms portrays tragedy that takes place among ordinary people, while the Javanese Chronicle story of Rara Oyi depicts tragedy of Rara Oyi, an ordinary but beautiful young lady vied by two noblemen, the king Sunan Amangkurat I of the kingdom of Islamic Mataram and his own crown prince, Pangeran Adipati Anom alias Prince Tejaningrat.   The analysis focuses on comparing the tragedy that befall either the protagonists or the antagonists in both the play and the chronicle account mentioned above. It turns out that their lives are in ruins due to their fate as they are not able to realize their dream of living with the lady they are madly in love with and wish to marry.